Inhibition of MYC attenuates tumor cell self‐renewal and promotes senescence in SMARCB1‐deficient Group 2 atypical teratoid rhabdoid tumors to suppress tumor growth in vivo - Alimova, Irina; Pierce, Angela; Danis, Etienne; Donson, Andrew; Birks, Diane K.; Griesinger, Andrea; Foreman, Nicholas K.; Santi, Mariarita; Soucek, Laura; Venkataraman, Sujatha; Vibhakar, Rajeev (International journal of cancer, 2019)
Loss of SMARCB1 is the hallmark genetic event that characterizes rhabdoid tumors in children. Rhabdoid tumors of the brain (ATRT) occur in young children and are particularly challenging with poor long‐term survival. SMARCB1 is a member of the SWI/SNF chromatin remodeling complex that is responsible for determining cellular pluripotency and lineage commitment. The mechanisms by which SMARCB1 deletion results in tumorigenesis remain unclear. Recent studies demonstrate that ATRT consists of 3 genomic subgroups with a subset of poor outcome tumors expressing high BMP and MYC pathway activation. Here we show that MYC occupies distinct promoter loci in ATRT compared to embryonic stem (ES) cells. Furthermore, using human ATRT cell lines, patient‐derived cell culture, ex vivo patient‐derived tumor, and orthotopic xenograft models, we show that MYC inhibition is a molecular vulnerability in SMARCB1‐deleted tumors and that such inhibition effectively suppresses BMP and pluripotency‐associated genomic programs, attenuates tumor cell self‐renewal, promotes senescence, and inhibits ATRT tumor growth in vivo. Transgenic expression of Omomyc (a bona‐fide MYC dominant negative) or chemical inhibition of MYC transcriptomic programs with the BET inhibitor JQ1 phenocopy genetic depletion of MYC, effectively restricting ATRT tumor growth and opening a promising therapeutic avenue for rhabdoid tumors in children. What's new? Atypical teratoid rhabdoid tumor (ATRT) is a devastating childhood tumor characterized by deficiency of the SMARCB1 chromatin remodeling protein. This major defect is accompanied by high heterogeneity in gene transcription, enabling ATRTs to be classified into genomic subgroups. This study shows that in Group 2 ATRTs, characterized by high BMP pathway activation, the MYC oncogene is involved in tumorigenesis, exhibiting unique promoter occupancy. In experiments in ATRT cells and animals, MYC inhibition by genetic and chemical means blocked ATRT tumorigenesis by suppressing cellular pluripotency and promoting senescence. The study identifies MYC as a promising therapeutic target in SMARCB1‐deleted tumors.